Short- and long-term impact of a physical exercise intervention on physical capacity and perceived physical work ability among middle aged women - Nygård, Maria (2018)
Only a fifth of the Finnish adult population fulfill the national recommendations for health-enhancing physical activity and 36% experience their work to be physically demanding.